Sosialisasi dan Pelatihan Digital Marketing sebagai Strategi Pengembangan UMKM Desa Kayunan, Kayunan, Plosoklaten, Kediri - Khasanah, Putri Nurul; Rohmah2, Ulfi At-Tiqohtur; Hidayah, Nurma; Alfandi, Moh.; Azani, Sadik; Fatimatuzzahro, Maudy; Azkiyah, Dzurrotul Maulidah; Setiawan, Wahyu Firman; Putri, Ermalinda Oktavera; Ni'mah, Faiqotun; Akbar, Arya Fadila; Sari, Dewi Dita; Mak'isyah, Yusrina Al; Wijaya, Intan Syamsyyana; Ibriziyah, Ibriziyah; Febianti, Risania; Rosa, Selvia Dia; Surahmat, Surahmat (Welfare : Jurnal Pengabdian Masyarakat, 2024)
Digital marketing has become a basic need for business actors, including MSMEs in Kayunan Village which is known for producing rengginang crackers and cassava crackers. With the change in consumer behavior from traditional to digital, MSMEs are required to adapt and utilize digital technology to increase competitiveness. However, many MSMEs do not fully understand how to use digital tools effectively. The method used is the ABCD approach. Through digital marketing outreach activities, MSMEs in Kayunan Village are given a basic understanding of the use of social media platforms, how to create interesting content, and manage online advertising efficiently. The results of the activity showed that participants responded positively and understood the importance of digital marketing to reach a wider market, increase visibility and increase sales of their products. It is estimated that by implementing optimal digital marketing strategies, MSMEs in Kayunan Village can develop more rapidly and contribute to improving the local economy.